Dependable Software Engineering: Theories, Tools, and Applications First International Symposium, SETTA 2015, Nanjing, China, November 4-6, 2015, Proceedings - Li, Xuandong; Liu, Zhiming; Yi, Wang.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the First International Symposium on Dependable Software Engineering: Theories, Tools, and Applications, SETTA 2015, held in Nanjing, China, in November 2015. The 20 full papers presented together with 3 invited talks were carefully reviewed and selected from 60 submissions.The papers are organized on topical sections on probabilistic systems; hybrid and cyber-physical systems; testing, simulation and inference; bisimulation and correctness; design and implementation; symbolic execution and invariants; and verification and case studies.
Keywords: Computer science; Software engineering; Computer logic; Mathematical logic; Computer simulation; Computer Science; Software Engineering; Logics and Meanings of Programs; Simulation and Modeling; Mathematical Logic and Formal Languages; Electronic books